A descoberta do elétron como tema gerador de um ensino de física mediado por experimentação remota - Cardoso, Dayane Carvalho (2016)
In this work, we have proposed and applied a methodology for teaching electromagnetism, based on an experimental activity and designed in an investigative teaching model, and containing a high degree of dialogism among teachers and students. We have used the discovery of the electron as a generator theme and a remote experiment to determine the charge-to-mass ratio of the electron as an educational resource. Our analyses indicate favorably towards the promotion of ways of appropriation of knowledge by the student, very different from those perceived in traditional expositive classes. Similarly, we find that the presence of a technological resource and an experimental activity create new posture of the teacher in the classroom, probably caused by the unpredictability of the results from the use of such resources. A challenge that we still need to solve is how to engage students in extra classroom tasks, since learning is not only effective in time for classes. We also present the weaknesses detected in our methodological proposal as well as implementations necessary in order to continue the validation process of this methodology.